2017
DOI: 10.1039/c6gc03589b
|View full text |Cite
|
Sign up to set email alerts
|

Atom economical synthesis of N-alkylbenzamides via the iron(iii) sulfate catalyzed rearrangement of 2-alkyl-3-aryloxaziridines in water and in the presence of a surfactant

Abstract: A green preparation of N-alkylbenzamides involves synthesis of 2-alkyl-3-aryloxaziridines from N-alkylamines and benzaldehydes followed by iron(iii) sulfate catalyzed rearrangement to the corresponding amides in water and in the presence of sodium dodecyl sulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Amides, as one of the most important classes of N-containing organic compounds, are known to be present in proteins, natural products, bioactive compounds, and agrochemicals . In recent years, constant efforts have targeted efficient catalytic methods for the construction of the omnipresent amide bond . Despite significant advancement in this area, there is still a continuing need for development of new synthetic methods for amide bond synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Amides, as one of the most important classes of N-containing organic compounds, are known to be present in proteins, natural products, bioactive compounds, and agrochemicals . In recent years, constant efforts have targeted efficient catalytic methods for the construction of the omnipresent amide bond . Despite significant advancement in this area, there is still a continuing need for development of new synthetic methods for amide bond synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Ollevier and co-workers also reported that in the presence of SDS, iron­(III) sulfate could catalyze the rearrangement of 2-alkyl-3-aryloxaziridines in water to afford the desired N -alkylbenzamides in excellent yield (Scheme ). The reaction only afforded the products in low yield without SDS, even at raised temperatures. The authors also compared the atom economy and the generated waste to those reported previously.…”
Section: Surfactant-based Catalystsmentioning
confidence: 99%
“…Indeed, DMC is well-known as safe reagent and solvent that has been used for many green applications [ 31 33 ]. On the other hand, water is a simply and environmentally benign solvent and interest has increasingly turned to it as the greenest solvent of chemical reactions [ 34 ]. In order to find the best reaction conditions, a model reaction was chosen using (L)-alanine phenylhydrazide ( 3a , Scheme 3 ), and the results of these optimized studies were summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%